Effect of small-sided games rule changes on time spent in different intensity zones, frequency of technical actions and distance covered during soccer training - Abdullah, Muhammad Taufiq Cheng (2016)
This study aims to examine physiological factors such as the amount of time spent in three intensity zones (low, moderate, high), frequency of technical actions, and distance covered during soccer training utilizing four separate small-sided games (SSGs: 5 vs. 5 plus two goal keepers) with different rule changes (free-touches, SSGFT; one-touch, SSG1T; two-touches, SSG2T; three-touches, SSG3T) in Malaysian Super League (MSL) soccer players. Twelve men’s soccer players, the first 11 starting players plus the reserve goal keeper (mean + SD: age, 24.3+4.0 years; height, 171.2+5.9 cm; weight, 61.9+7.4 kg) participated in the study. Variables like the amount of time spent in different heart rate (HR) zones and distance covered were recorded using electronic heart-rate monitors and global positioning systems while technical actions were quantified from video recording. This research was conducted using an experimental research design with repeated measures. SSG2T and SSGFT induced longer time spent in the high-intensity heart rate zone (p = 0.001) while SSG1T made players spend a longer duration in the moderate-intensity zone (p = 0.001) compare to all other SSGs. For technical actions, SSG1T was better for achieving successful passing (p = 0.001). SSG1T and SSG3T were better in interceptions (p = 0.001). SSGFT created the highest number of shots on goal and crossing (p = 0.001). There were no significant differences in goals scored (p = 0.537) and the distance covered (p = 0.574) during SSGs performance. The essential findings reveals that changes in SSGs playing formats influence training intensity, frequency in technical actions, and distance covered by soccer players during training. Rules with moderate number of touches (SSG2T) are seen to increase the team's chances to score and increase training intensity. These results suggest that SSGs training with different formats are more suitable to specific playing positions such as SSG1T and SSG2T for midfielders, SSGFT and SSG2T for strikers, and SSG1T and SSG3T games for defenders. Finally, the present study suggests that all factors that influence SSGs training should be considered and implemented so that training becomes more complete and reflects actual competitive situations.